1979
DOI: 10.2307/1942573
|View full text |Cite
|
Sign up to set email alerts
|

Pollination and Wind Dispersal of Pollen in Arceuthobium

Abstract: The mode of pollination was studied in 2 dwarf mistletoes, Arceuthobium douglasii and A. strictum, from Utah and northern Mexico. Insect visitations to the staminate flowers of A. strictum were common. Visits were found to be rare, however, to the pistillate flowers and to either sex of A. douglasii. Pollen was found to be consistently liberated by the wind from the well—exposed anthers. Air—borne pollen concentration decreased rapidly with distance from the source. No inferences, however, could be made from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Large clumps of pollen like those observed during pollen shedding were rarely observed in pollen samples collected above the canopy, indicating that clump breakdown occurs relatively quickly. Our hypothesis of turbulent disaggregation of pollen clumps explains observations by Player (1979) and Lisci et al (1996) that pollen clump size tended to be inversely proportional to mean wind velocity; higher wind velocities generate more turbulence in environmental flows, which would more quickly and thoroughly disaggregate pollen clumps. It should be noted that previous researchers describe for the initially released pollen clumps a period of adherence to surrounding vegetation before eventual entrainment into the lower atmosphere (Bianchi et al, 1959).…”
Section: Resultssupporting
confidence: 60%
“…Large clumps of pollen like those observed during pollen shedding were rarely observed in pollen samples collected above the canopy, indicating that clump breakdown occurs relatively quickly. Our hypothesis of turbulent disaggregation of pollen clumps explains observations by Player (1979) and Lisci et al (1996) that pollen clump size tended to be inversely proportional to mean wind velocity; higher wind velocities generate more turbulence in environmental flows, which would more quickly and thoroughly disaggregate pollen clumps. It should be noted that previous researchers describe for the initially released pollen clumps a period of adherence to surrounding vegetation before eventual entrainment into the lower atmosphere (Bianchi et al, 1959).…”
Section: Resultssupporting
confidence: 60%
“…With the exception of the Viscaceae genus Arceuthobium , in which nectar‐offering and fly‐pollinated species may sometimes receive wind‐carried conspecific pollen (Player, 1979), parasitic species are animal‐pollinated, with all pollinator categories from vertebrates to insects represented (Table 1). Figure 4 shows some of the pollination syndromes represented (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Biological assumptions concerning the role of size, shape and density used in the model are also justifiable (see Whitehead, 1969;Harrington, 1979;Player, 1979). The behavior of airborne biological structures (spores, pollen, seeds, fruits) will vary depending upon such factors as the speed of descent, the height of release, wind speed/turbulence and morphological adaptations for dispersal (Gregory, Longhurst, and Sneeramula, 1961;Sneeramula and Ramalingam, 1961;Csanady, 1963;Watkinson, 1978;Chamberlain, 1975;Tonsor, 1985;Augspurger and Franson, 1987).…”
Section: Results-wind-tunnel Exp Eriments-thementioning
confidence: 99%
“…Empirically, it has also been shown that some plants may be able to preferentially capture conspecific pollen grains. Although preferential pollen capture may be the exclusive result of the morphology ofovulate organs, there are a number ofreasons for inferring that the physical properties ofpollen grains play an equally important role: the density and size of an object will determine in part the extent to which the object settles out of a transport medium (Dyakowska and zycki, 1959;Harrington, 1979;Player, 1979). Thus, the shape, size, and density of pollen grains may vary intra-and interspecifically.…”
mentioning
confidence: 99%